The effect of aging on sputum inflammation and asthma control - Busse, Paula J. (J Allergy Clin Immunol, 2016)
BACKGROUND: Aged asthma patients experience increased morbidity and mortality. Knowledge of the aging effect on airway inflammation and asthma control is limited. OBJECTIVE: To compare airway inflammation and its relationship with asthma control in aged vs. younger patients and determine if differences are asthma-specific or due to “inflamm-aging.” METHODS: Prospective study of aged (>60 years) and younger (21–40 years) inner-city asthma patients. After a run-in period to control for inhaled corticosteroid use, induced sputum was collected. Aged-matched, non-asthma controls were included to measure age-related inflammatory changes. RESULTS: Aged (mean age 67.9±5.1 years, n=35) compared to younger (mean age 30.8±5.9 years, n=37) asthma patients had significantly worse asthma control and lower forced expiratory volume in one-second (FEV(1)). Aged asthma patients had higher sputum neutrophil number and percent (30.5 ×10(4)/mL and 23.1%) and eosinophils (7.0×10(4)/mL and 3.8%) compared to younger patients (neutrophils, 13.0 ×10(4)/mL [P<0.01] and 6.9% [P<0.01]; eosinophils, 2.0×10(4)/mL [P <0.01] and 1.2% [P<0.01]). Aged asthma patients had higher sputum interleukin-6 (IL-6) (P <0.01) and IL-8 (P =0.01). No significant inflammatory differences between aged and younger controls were observed. In aged asthma patients, elevated sputum IL-6 and MIP3α/CCL20 were significantly associated with decreased asthma control; elevated sputum neutrophils, IL-1β, IL-6 and MIP3α/CCL20 with hospitalization. CONCLUSIONS: The inflammatory patterns of aged vs. younger asthma patients are associated with increased sputum neutrophils and eosinophils and cytokines related to neutrophil recruitment. Differences in airway inflammation may contribute to diminished asthma control in the aged. Further understanding of asthma pathophysiology in aged patients is needed to improve management of this vulnerable population.